Short-term variability of copepod abundance in Jurumirim Reservoir, São Paulo, Brazil - E. A. PANARELLI (Brazilian Journal of Biology)
Short-term variability in composition and abundance of copepod populations were studied during the dry (winter) and rainy (summer) seasons, at the dam region of Jurumirim Reservoir, São Paulo, Brazil. An intensive sampling program was carried out during 30 days in each period of the year. Samples and measurements were taken every other day at 0, 5, 10, 15, 20 and 25 m depths. The relationship between variability of the populations and some environmental factors was analyzed. The main species were: Argyrodiaptomus furcatus (Sars), Notodiaptomus iheringi (Wright), Mesocyclops longisetus (Thiébaud), Thermocyclops decipiens (Fischer), and T. minutus (Lowndes). Thermocyclops minutus was the most abundant species in dry season and its abundance varied significantly between sampling days. A large increase in abundance of calanoids occurred during the rainy season. This increase was correlated with higher temperature values. At that time, Notodiaptomus iheringi was dominant. This species showed significant short-term variations in abundance in both dry and rainy seasons. Significant variation in density of populations within the same sampling period might result from either the dispersion pattern of the populations or continuous substitution of the water masses. Significant correlation was observed between copepod abundance and temperature, especially for species of calanoids and there was also some correlations between densities of particular species of copepods and some phytoplankton taxa, mainly during the dry season. As for vertical distribution, most organisms were found between the surface and 15 m deep. During the rainy season, there was some evidence of the occurrence of spatial segregation between species of cyclopoids and calanoids, with the cyclopoids in a deeper position within the water column.